Endoluminal grafting in the treatment of iliac and superficial femoral artery disease. - Diethrich, E B (1997)
Treatment of iliac artery disease with stents has been generally successful; however, disease in the smaller arteries below the inguinal ligament has been more resistant to percutaneous intervention techniques. Ongoing research is evaluating the potential value of newer, more flexible stents as well as the use of covered endoluminal grafts to "reline" diseased arterial segments. It is possible that intimal hyperplasia may be reduced by covering the stent on one or both sides with a fabric such as polytetrafluoroethylene, yielding improvements in long-term patency. A number of device manufacturers have developed Investigational Device Exemption protocols with the Food and Drug Administration to allow randomized comparison of covered grafts and uncovered stents. The use of endoluminal grafts in the treatment of large aneurysms involving the common and internal iliac arteries and the origin of the external iliac artery is also under investigation; this application may prove advantageous, since operative intervention in these locations is often difficult. In addition, the endoluminal graft has been used to manage traumatic or iatrogenic rupture of an iliac artery, and the use of systems incorporating nitinol stents for an "internal" femoropopliteal bypass procedure is also being studied. Although aneurysmal disease in the superficial femoral artery is uncommon, the use of endoluminal grafts now makes it possible to treat these lesions percutaneously with an intraluminal approach; endoluminal graft exclusion of aneurysmal disease in the popliteal artery is also promising.